Effect of Thickness and Radius on the Springback of Bent Rubberwood - Jalaludin, Zaihan (2001)
Knowledge on springback and moisture uptake is necessary in assessing the potential use of bentwood in furniture industry. In this study Rubberwood was used for making bentwood. Factors such as storing condition, thickness and radius on the bending properties were studied. The specimens were plasticised by soaking in hot water for 1 hour and steamed for 25 minutes. The specimens were placed inside a stainless steel strap and pressed in a moulded hot press at three radius of curvatures (600mm, 900mm and 1200mm). The bent specimen was further heated for setting the bentwood. The springback assessments were carried out by exposing the bentwood to two different conditions: workshop (23.0°C to 33.5°C and RH 67 % to 96%) and air-conditioned room (25°C and RH 70%). The results show the springback and the moisture uptake were high in the workshop condition. Storage condition and thickness had significant effect influence on the moisture uptake and springback but radius has no significant difference. Air-conditioned room can be used as storage for bentwood in order to minimise the moisture uptake and springback. The thicker bentwood had the lowest springback and moisture uptake. There was a strong linear relationship between the springback and the moisture uptake.